2010
DOI: 10.1155/2010/109063
|View full text |Cite
|
Sign up to set email alerts
|

Expression of HER2 in Colorectal Cancer Does Not Correlate with Prognosis

Abstract: Abstract. Estimation of HER2 membranous expression is routinely used in breast and gastric cancers, as both a prognostic and a predictive factor. To date there is no evidence for similar application of HER2 expression in colorectal cancer (CRC) cells. In CRC, HER2 is sometimes overexpressed in the cell membrane and very often in the cytoplasm. This study was conducted to determine possible correlations between both membranous and cytoplasmatic expression of HER2 in CRC cells and the outcome of the disease. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
35
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 23 publications
4
35
1
1
Order By: Relevance
“…Our study observed majority of colorectal cancers with cytoplasmic expression of Her-2/neu (48 %) which corresponds to the studies which followed all the three parameters of Her-2/neu evaluation [15,17,20,21]. In our series we found 26.6 % positivity for membranous Her- 2/neu staining.…”
Section: Discussionsupporting
confidence: 89%
“…Our study observed majority of colorectal cancers with cytoplasmic expression of Her-2/neu (48 %) which corresponds to the studies which followed all the three parameters of Her-2/neu evaluation [15,17,20,21]. In our series we found 26.6 % positivity for membranous Her- 2/neu staining.…”
Section: Discussionsupporting
confidence: 89%
“…Asian Pacific Journal of Cancer Prevention, Vol 15, 2014 5555 DOI:http://dx.doi.org/10.7314/APJCP.2014.15.14.5551 Lack of Effects of HER-2/neu on Prognosis in Colorectal Cancer: a Meta-analysis al., 2009Kruszewski et al, 2010). In our meta-analysis, two prospective studies and five studies of Asian patients revealed HER-2/neu to be a worse prognostic factor for CRC without significant heterogeneity.…”
Section: Discussionmentioning
confidence: 67%
“…[6][7][8][9][12][13][14][15][16][17][18][19][20] The present study is unique because the only study with an equally large sample size, albeit without clinical validation, reported much lower rates of both ERBB2 expression (2.7%) and positive amplification (1.6%). 8 This difference very likely resides in the fact that while our findings have been obtained on a primarily metastatic population, Heppner et al 8 tested only primary tumors using a different staining antibody (SP3) and a different in situ hybridization method (CISH), and employed gastric cancer criteria to test and score the samples.…”
Section: Discussionmentioning
confidence: 97%
“…These are routinely used to establish ERBB2 status in breast and gastric cancer but have not been customized for colorectal cancer for which the reported rate for ERBB2 positivity ranges enormously from o1% to 450%. [6][7][8][9][12][13][14][15][16][17][18][19][20] The aim of the present study was to develop a validated ERBB2 scoring system for colorectal cancer with the goal of identifying ERBB2-positive patients suitable for enrollment in the HERACLES trial.…”
mentioning
confidence: 99%